Anxiety, depression and defense mechanisms associated with treatment decisional preferences and quality of life in non‐metastatic breast cancer: a 1‐year prospective study. Issue 11 (27th May 2013) - Hyphantis, Thomas; Almyroudi, Augoustina; Paika, Vassiliki; Degner, Lesley F.; Carvalho, André F.; Pavlidis, Nicholas
Abstract: Objective: Treatment decisional preferences impact breast cancer patients' health‐related quality of life (HRQoL) and may relate to psychological variables, although many aspects of this relationship remain unknown. This prospective study aimed to assess psychological correlates of treatment decisional preferences and predictors of HRQoL in women with early non‐metastatic breast cancer. Methods: Of the 124 women initially assessed for anxiety (Spielberger's State–Trait Anxiety Inventory) and depressive (Center for Epidemiologic Studies‐Depression (CES‐D)) symptoms, HRQoL (WHOQOL‐BREF), and defense mechanisms (Life Style Index), 82 (66.1%) completed the 1‐year follow‐up. Mean age was 54.6 years (SD = 9.76), and mean disease duration was 19.4 months (SD = 25.55); 19.5% had stage I, 63.4% stage II and 17.1% stage III disease. The predictive power and moderator effects of psychological variables were tested using multiple and hierarchical regression models. Results: Depressive symptoms and physical HRQoL improved significantly, state anxiety and mental and environment HRQoL remained stable, and social relations HRQoL deteriorated over the 1‐year period. Older age ( p = 0.021) and higher scores in repression defense ( p = 0.044) were independently associated with passive decisional preferences. Earlier stage of cancer ( p = 0.043), lower state anxiety ( p = 0.039), lower repression scores ( p = 0.021) and improvement in depressive symptoms ( p < 0.001) predicted physical HRQoL improvement. Moderation analysis showed that active decisional preferences predicted physical HRQoL improvement, but only in those women with lower repression levels. Conclusions: Defense mechanisms are associated with treatment decisional preferences and interact with factors predicting HRQoL in women with breast cancer. Clinicians should address the patients' anxiety and depressive symptoms and refer patients with high repression tendencies for psychological evaluation and management. Copyright © 2013 John Wiley & Sons, Ltd.